Influence of CYP2C9 Polymorphisms on Plasma Concentration of Warfarin and 7-Hydroxy Warfarin in South Indian Patients - Kumar, Dhakchinamoorthi K.; Uppugunduri, Chakradhara R. S.; Shewade, Deepak Gopal; Chandran B.V., Sai; Adithan, Chandrasekaran (Current Drug Metabolism, 2021)
Background: Warfarin is primarily metabolized by cytochrome P450 2C9 (CYP2C9) enzyme, which is encoded by the CYP2C9 gene. CYP2C9*2 and CYP2C9*3 variants significantly influence warfarin metabolism and subsequently the required dose of warfarin. Objectives: The current retrospective study was aimed to determine the influence of CYP2C9 variants on warfarin metabolic ratio (MR, warfarin/7-hydroxy warfarin) and warfarin maintenance therapy in 210 patients (mean age 44.6±11.6 (SD) years; male to female ratio 81:129). Methods: High-performance liquid chromatography (HPLC) with UV detector was used to measure plasma concentrations of warfarin and 7-hydroxy warfarin. Plasma samples were collected 12 h after the previous dose of warfarin was administered. CYP2C9 variants (rs1799853 and rs1057910) were identified using real-time polymerase chain reaction allele-discrimination method. Results: The mean daily maintenance dose of warfarin was 4.6±1.8 (SD) mg. The mean plasma warfarin and 7-hydroxy warfarin concentrations were 3.7±1.6 (SD) μg/mL and 1.1±0.54 (SD) μg/mL, respectively. Patients carrying other CYP2C9 variants required 39% lower warfarin maintenance dose 3.3±1.2(SD)mg than CYP2C9*1*1 carrier 4.9±1.8(SD)mg, (p<0.0001). MRs differed significantly between CYP2C9 variant carriers (8.1±5.1) and normal genotype carriers (4.8±3.9) (p<0.0001). Probit analysis identified an MR value of 7.6 as the anti-mode (sensitivity of 84% and specificity of 55%) to differentiate poor and intermediate metabolizers (carriers of any CYP2C9*2 or CYP2C9*3 variants) from normal metabolizers (CYP2C9*1*1 genotype). Conclusion: The present study results provide, insights on the effect of CYP2C9 genetic polymorphisms on inter-individual variability in warfarin metabolism and emphasizes utility of phenotyping in a setting of genotype-guided dosing of warfarin in South Indian population.
Keywords: metabolism